Analysis of the Effect Variation of Sides Racing Bike Helmets on Flow Characteristics Using CFD - Syamsuri, Syamsuri; Lillahulhaq, Zain; Mufarrichi, Muhammad (TURBO [Tulisan Riset Berbasis Online], 2024)
The selection of materials and aerodynamic design forms needs to be considered in designing a comfortable helmet. The emergence of the drag force on the helmet causes a compressive force, which causes the rider discomfort when driving at high speeds. This research was conducted on 4 variations of helmet models consisting of 1 time-trial type helmet as a reference and 3 other helmets which were developed from the basic model. This simulation was conducted in a 2D helmet model at Re 7.14 x 104, 1.00 x 105, and 1.16 x 105. In this study, Turbulence Intensity was varied as 0.1%, 0.2%, and 1%. The results are shown through the drag coefficient's value and visualization of streamlined flow. The results showed that the 2D simulation on the helmet produced a lower error by using Set Up Turbulence Intensity 0.1%. The emergence of the Oscillating Karman vortex in large size indicates the higher the drag force that occurs on the helmet. In this study, helmet type 3, with a trailing edge and has a smooth curve, has the lowest drag force at Re 1.16 x 105 with a drag coefficient value of around 0.38.